Studi Pengaruh Kualitas Air Hujan terhadap Kelangsungan Hidup (Survival Rate) Benih Ikan Komet (Carassius auratus) - Nida Awwalia; Ujang Dindin; Novita MZ (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
Rainwater is often considered to have a negative impact on the survival of fish fry, mainly due to its slightly acidic pH. However, this study aims to investigate the effect of rainwater on the survival rate of comet fish fry (Carassius auratus). The research was conducted at the Bossbaster experimental pond, Legok Nyenang Village, Kadudampit District, Sukabumi Regency, over a period of three days. The fish fry used were one day old after hatching, with a size of approximately 5 mm. The study utilized 15 containers with a water volume of 10 liters per gallon and 15 aeration devices to maintain water circulation. Five treatments were tested: A (100% rainwater), B (75% rainwater), C (50% rainwater), D (25% rainwater), and E (0% rainwater). The research design followed a Randomized Complete Block Design (RCBD) with three replications for each treatment. The data were analyzed using the Median Test and Regression Test to maximize the obtained results. The results showed that rainwater did not significantly affect the survival rate of comet fish fry. The survival rate of the fry in all treatments ranged from 98.33% to 99.17%. This indicates that although rainwater has a lower pH, it does not significantly affect the survival of comet fish fry. Based on these findings, it can be concluded that the rainwater taken from the research site did not negatively impact the survival rate of comet fish fry. The quality of the rainwater used in this study is safe and can be used as a medium for raising fish fry without causing a decrease in their survival rate. This study provides valuable information on the use of rainwater in fish farming, especially for comet fish fry.